Brain Metastases in Oncogene-Addicted Non-Small Cell Lung Cancer Patients: Incidence and Treatment - Remon, J.; Besse, Benjamin (Frontiers in Oncology, 2018)
Brain metastases are common in non-small cell lung cancer (NSCLC) patients including in molecularly selected populations such as EGFR-mutant and ALK-rearranged tumours. They are associated with a reduced quality of life, and are commonly the first site of progression for patients receiving tyrosine kinase inhibitors (TKIs). In this review we summarize incidence of brain metastases and intracranial efficacy with TKI agents according to oncogene driver mutations, focusing on important clinical issues, notably optimal first-line treatment in oncogene-addicted lung tumours with upfront brain metastases (local therapies followed by TKI versus TKI monotherapy). We also discuss the potential role of newly emerging late-generation TKIs as new standard treatment in oncogene-addicted lung cancer tumours compared with sequential strategies.